NEUROPHARMACOLOGICAL EFFECTS OF NIGERIAN HONEY IN MICE - Akanmu, M. O. A.; Olowookere, T. A.; Atunwa, S. A.; Ibrahim, B. O.; Lamidi, O. F.; Adams, P. A.; Ajimuda, B. O.; Adeyemo, L. E. (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Honey is a natural sweet substance that bees produce by transforming flower nectar or other sweet secretions of plants. It has widespread use in traditional medicine in various parts of the world. It has been reported to assist in building the entire central nervous system. The beneficial effects of honey have been attributed to the possible polyphenolic contents and some other constituents. The geographical locations and the sources of plant nectars may contribute to the effects of honey samples. Thus, we evaluated the neuropharmacological effects of six samples of honey (10%, 20% and 40%V/v, p.o.) from three geographical locations of Nigeria using the following behavioral models: Novelty-induced behaviors (NIB), learning and memory, pentobarbital-induced hypnosis, anxiolytic, anticonvulsant, analgesic and antidepressant models in mice. The results showed that honey significantly (p< 0.05) decreased locomotion and rearing behaviors in NIB and amphetamine-induced locomotor activity when compared to the control group. Exploratory behavior was significantly increased in both holeboard and elevated plus maze but had no significant effect on spatial working memory. Honey sample from Umudike has significant hypnotic and anticonvulsant effects. The antinociceptive models (hot plate and tail flick tests) showed that the honey samples significantly increased the pain reaction time and naloxone blocked these central antinociceptive effects. The force swimming test showed that only the Idanre (ID) honey sample had antidepressant effect. In conclusion, some of these honey samples have central inhibitory property, anxiolytic, antinociceptive, anticonvulsant and antidepressant effects, thus may be used as nutraceutic. It can also be inferred that some of these effects are probably mediated through dopaminergic and opioidergic systems.